2005
DOI: 10.1111/j.1365-2958.2005.04867.x
|View full text |Cite
|
Sign up to set email alerts
|

LexA regulates the bidirectional hydrogenase in the cyanobacterium Synechocystis sp. PCC 6803 as a transcription activator

Abstract: SummaryThe bidirectional NiFe-hydrogenase of Synechocystis sp. PCC 6803 is encoded by five genes ( hoxEFUYH ) which are transcribed as one unit. The transcription of the hox -operon is regulated by a promoter situated upstream of hoxE . The transcription start point was located at − − − − 168 by 5 ′ ′ ′ ′ Race. Several promoter probe vectors carrying different promoter fragments revealed two regions to be essential for the promoter activity. One is situated in the untranslated 5 ′ ′ ′ ′ leader region and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 69 publications
7
105
2
Order By: Relevance
“…The LexA-like protein binds two sites in the hydrogenase (hox) operon and may function as a transcription activator (Gutekunst et al, 2005;Oliveira & Lindblad, 2005). Consistent with this, we observed that transcript levels of the hox operon (sll1220-sll1226) increased in both strains under low oxygen (Table 2).…”
Section: The Absence Of Hik31 Alters Transcriptional Response To Low supporting
confidence: 75%
“…The LexA-like protein binds two sites in the hydrogenase (hox) operon and may function as a transcription activator (Gutekunst et al, 2005;Oliveira & Lindblad, 2005). Consistent with this, we observed that transcript levels of the hox operon (sll1220-sll1226) increased in both strains under low oxygen (Table 2).…”
Section: The Absence Of Hik31 Alters Transcriptional Response To Low supporting
confidence: 75%
“…4 shows the hydrogenase operon which encodes all proteins required for pentameric bidirectional Ni-Fe hydrogenase (HoxEFUYH). This operon uses a single TSS located 168 nt upstream of hoxE (19), and its regulation is well studied (19)(20)(21). Intriguingly, we found that the operon is framed by two highly expressed ncRNAs, one of which [SyR1 (14)], was strongly upregulated under high light, whereas the other (ncr0700) was maximally expressed in the dark (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Second, in the cyanobacterium Synechocystis sp. PCC 6803, LexA has been found to activate expression of the hox operon, which encodes the bidirectional NiFe-hydrogenase of this organism (Gutekunst et al, 2005). In addition, the dnaB gene and the predicted coding region CC_2433 from Caulobacter crescentus are downregulated in a lexA mutant, and both genes contain SOS boxes with significant scores.…”
Section: Is Lexa Involved In Transcriptional Activation Of Sos Gene Ementioning
confidence: 99%